1994
DOI: 10.1039/p19940002921
|View full text |Cite
|
Sign up to set email alerts
|

ortho-Arylation of 3,5-di-tert-butylphenol with aryllead(IV) derivatives: a facile synthesis of sterically hindered phenols

Abstract: Faculte des Sciences St Jerbme, 73397 Marseille Cedex 20, France The reaction of aryllead(iv) triacetates with 3,5-di-tert-butylphenol 1 has been shown to yield very hindered 2-aryl-3.5-di-tert-butylphenols and 2,6-diaryl-3,5-di-tert-butylphenols such as 15 and 16. The mechanism of this arylation reaction with aryllead(iv) derivatives is discussed. A free radical pathway has been excluded. The favoured pathway must involve the occurrence of covalent aryl(ary1oxy) lead(iv) diacetate intermediates, although they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…85,86 Furthermore, Bi(V) phenoxides have been isolated and characterized for electron-poor phenols, and have been shown to undergo ligand coupling upon heating. 87 The divergent chemoselectivity exhibited by bismacycles 50 and 51 has parallels in other systems based on bismuth(V), 60 iodine(III) 88,89 and lead(IV), 90,91 each of which engage phenols in either oxidation or aryl-transfer processes as a function of the ligands at the metal center. 13 While the basicity of the ligands associated with Bi(V) clearly differentiates 50 and 51, the dimeric nature of the former may also contribute to the observed chemoselectivity differences.…”
mentioning
confidence: 87%
“…85,86 Furthermore, Bi(V) phenoxides have been isolated and characterized for electron-poor phenols, and have been shown to undergo ligand coupling upon heating. 87 The divergent chemoselectivity exhibited by bismacycles 50 and 51 has parallels in other systems based on bismuth(V), 60 iodine(III) 88,89 and lead(IV), 90,91 each of which engage phenols in either oxidation or aryl-transfer processes as a function of the ligands at the metal center. 13 While the basicity of the ligands associated with Bi(V) clearly differentiates 50 and 51, the dimeric nature of the former may also contribute to the observed chemoselectivity differences.…”
mentioning
confidence: 87%
“…A related rearrangement within this category is the migration of aryl groups from phenolate–metal complexes (Scheme ). Barton introduced Pb­(IV) and Bi­(V) reagents for this purpose as early as 1985. More recently, Yamamoto reported asymmetric variants that employ chiral amine ligands to install biaryl bonds with good atroposelectivity .…”
Section: C2 Functionalizationmentioning
confidence: 99%
“…To illustrate the effect of acetyl groups of arylleads on the enantioselectivity, 2-isopropylphenyllead tribenzoate (13) was prepared from lead tetrabenzoate 25 by the procedure described by Pinhey. 21c The reaction between aryllead tribenzoate 13 and a Unless otherwise specified, reactions were performed using lithiated phenol (1 equiv), aryllead (2.5 equiv), MS 4 Å (3 g/mmol), brucine (6 equiv) in toluene.…”
Section: Phenol or Aniline Coupling With Aryllead Triacetatesmentioning
confidence: 99%
“…13 The reaction using arylleads as an equivalent of aryl cation was originally devised by Pinhey, who demonstrated that the use of excess pyridine accelerated the reaction rate (Scheme 1). 14 In marked contrast, anilines and anilides do not undergo either C-or N-arylation with aryllead triacetates.…”
Section: Introductionmentioning
confidence: 99%